PERANCANGAN SISTEM INFORMASI MONITORING OUTPUT DAN DEFECT PRODUKSI BERBASIS DESKTOP DENGAN MENGGUNAKAN METODE PROTOTYPING PADA PT JEKTRIM TECH INDONESIA - Arif Siswandi; Muhammad Iqbal Fadillah (Teknik Informatika, Universitas Pelita Bangsa, 2019)
The advancement of technology in the manufacturing sector made PT J. Ektrim Tech Indonesia have to change the production process of its goods to be computerized. So far, the production process which includes the process of reporting product results and repairing defective items for production is still done manually. The solution to this problem is to design a computerized manufacturing monitoring system. With this system, it is hoped that it can help the entire production process in the field, including being able to help make production defect data reports and assist production management in monitoring production activities. From the results of testing the application, it can be concluded that the system to be built using the prototyping method can manage product defect data and integrate production functions carried out by production management, production repairman and production scan operators into a series of production processes in production of PT J. Extreme Tech Indonesia. Keyword : Sistem monitoring manufaktur, metode prototyping, defect, produksi